(untitled) (Universal International Scientific Journal, 2026)
The models proposed in this article also consider the development of individual learning paths, teaching tailored to the needs of target groups, ensuring flexibility and diversity of learning formats, the use of modern educational technologies and IT, as well as the possibility of teaching teamwork skills (project-based group work).